2022
DOI: 10.18632/aging.203861
|View full text |Cite
|
Sign up to set email alerts
|

S-Klotho level and physiological markers of cardiometabolic risk in healthy adult men

Abstract: S-Klotho is perceived as a biomarker of healthy aging that has been shown to be inversely associated with cardiometabolic risk in elderly individuals. The aim of this study was to test if s-Klotho level is associated with cardiometabolic risk markers in younger healthy men in order to verify the possible role of s-Klotho level as an early marker of cardiometabolic risk. A cross-sectional study was conducted among 186 healthy men (Mage=35.33, SDage=3.47) from a Western urban population. Serum basal levels of s-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
(81 reference statements)
3
10
0
Order By: Relevance
“…We found that age strongly modified the negative association between α-Klotho and ACR, and this negative association was more pronounced in those aged ≥ 60 years than in those aged 40–59 years. This concurs with other findings indicating weaker effects of Klotho on relatively young individuals [ 56 , 57 , 58 ]. It is undeniable that most studies have focused on mid- to end-of-life applications, and data from early-life interventions are sparse and require a more robust evaluation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that age strongly modified the negative association between α-Klotho and ACR, and this negative association was more pronounced in those aged ≥ 60 years than in those aged 40–59 years. This concurs with other findings indicating weaker effects of Klotho on relatively young individuals [ 56 , 57 , 58 ]. It is undeniable that most studies have focused on mid- to end-of-life applications, and data from early-life interventions are sparse and require a more robust evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…The enhanced senescence of renal tubules and vascular cells leads to endothelial dysfunction and impaired vasculogenesis [ 61 ], suggesting the presence of complex physiologically relevant feedback loops. It cannot be excluded that genetic polymorphisms of the Klotho gene also contribute to such physical states [ 62 , 63 ], even in relatively young and healthy individuals [ 58 ]. Gender and BMI were not significant modifiers in our study, which has also been demonstrated in several human studies [ 8 , 64 ], as well as animal studies [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other research showing no relationship between s-Klotho level and health outcomes [114][115][116]. It is possible that the role of s-Klotho as a marker of biological age may depend on age and may be more valid in older individuals [113,117]. Also, other research suggested sex differences in the relationship between the s-Klotho level and health components [118] that might be explained by different pro les of sex hormones and the interaction between s-Klotho and testosterone or estradiol levels [119][120].…”
Section: Discussionsupporting
confidence: 92%
“…The procedure was described in detail previously [113]. In short, a fasting blood sample was taken between 7:30 a.m. and 9:00 a.m. for blood biochemical and hormone analyses.…”
Section: Methodsmentioning
confidence: 99%
“…One previous study demonstrated that testosterone can upregulate the expression of the klotho gene, and an additional study with a specific cohort revealed a positive relationship between testosterone and S-klotho in healthy sedentary middle-aged adults [ 23 , 24 ]. Another recent study assessed the relationship between testosterone levels and klotho in young males and also showed a positive correlation [ 25 ]. To the best of our knowledge, no research has been conducted to study the relationship between testosterone and S-klotho levels in males using a nationally representative population.…”
Section: Introductionmentioning
confidence: 99%